Control interno y administrativo en las operaciones de la exportación de cacao de la empresa exportadora Ayalma S.A. del cantón Quevedo año 2015 - Cano Anchundia, María Yessenia (2016)
This research work was carried out in the exporting company "Ayalma" SA, located in the Km1 Vía Principal Valencia, created on October 1, 2009, entitled "internal and administrative controls on the export operations of cocoa company Ayalma SA, canton Quevedo, 2015 "has been developed in order to assess the administrative processes of export and that for this investigation the following objectives: Conduct an assessment of the activities of the company, applying assessment tools efficiency and effectiveness of export operations; and issue a report on internal control of the export operations of the exporting company "Ayalma" S.A. By which use methods such as: inductive, with which pored over each of the elements of administrative processes; deductive, which allowed us to describe and conceptualize each of the activities carried out in the research process; and analytical, which was to dismember the elements of administrative processes to observe the causes, nature and effects. Where was obtained as a result that there are trained company personnel to improve their skills; has not been defined functions for each of the collaborators what constribuye duality of activities; and it does not have a procedure manual activities that improve, optimizen and minimize costs